PROPOSING BUILDING STRUCTURE toward Reducing the Greenhouse Gas Emissions : Life Cycle Assessment Analysis - Ali Tighnavard Balasbaneh,; David Yeoh,; Mohd Irwan Juki,; Rafidah Hamdan, (2022)
This book can be read by anyone who interested in construction and building renovation. Even with not high scientific background about sustainability and throughout, the book has been written with this audience in mind. The second group of readers will be represented by professionals from the construction industry, academia, and government agencies, especially project manager. I do not expect everybody in the scientific community to agree with the content and ideas put forth in this book. The book comprises nine chapters. Chapter 1 is a general introduction to Sustainability. Chapter 2 presents the methodology that has been used to assess the building material which we used the life cycle assessment. Chapter 3 introduces an element that has been applied in current research. Chapter 4 is defining the issues and challenging and explain why this study is essential to overcome the previous problem with timber construction. Chapter 5 is the result of comparing the current common materials andstructures in Malaysia. Chapter 6 is proposing a new building scheme combining timber and concrete. Chapter 7 is offering a new design for residential building combining wood and steel. Chapter 8 is proposing a new building scheme which incorporating engineering timber and steel. Finally, Chapter 9, we have a discussion and future research.